PENINGKATAN KEPERCAYAAN DIRI ANAK KORBAN PERCERAIAN DI DESA SAMPAGA KABUPATEN MAMUJU (PERSPEKTIF BIMBINGAN DAN KONSELING ISLAM) - Yusparini, Yusparini; Alimuddin, Nurwahidah; Zuhra, Zuhra (Nosipakabelo: Jurnal Bimbingan dan Konseling Islam, 2020)
This research entitled: Increasing the Confidence of Children Divorce Victims in Sampaga Village, Mamuju Regency (Islamic Guidance and Counseling Perspective). This research, is motivated by the number of children divorce victims in Sampaga Village, Mamuju Regency. The main problems in this research are: 1) How is the description of self-confidence children who are victims divorce. 2) what factors are supports and inhibits the increase of self-confidence children who are victims divorce. The objectives of this research are: 1) to find out how is the description of self-confidence children who are victims divorce in Sampaga Village, Mamuju Regency. 2) to determine the supporting and inhibiting factors for increasing self-confidence of children of divorce victims in Sampaga Village, Mamuju Regency. This research is conducted in qualitative research, And used observation, interviews and documentation in collection the data.